How longer can people live by achieving the daily ambient fine particulate pollution standards in the Pearl River Delta region, China?. (September 2020) - Ruan, Zengliang; Qian, Zhengmin (Min); Xu, Yanjun; Yang, Yin; Zhang, Shiyu; Hang, Jian; Howard, Steven; Acharya, Bipin Kumar; Jansson, Daire R.; Li, Huan; Sun, Xiangyan; Xu, Xiaojun; et al.
Abstract: Background: Previous research has reported the effects of long-term fine particulate matter (PM2.5 ) pollution on years of life lost (YLL), but these effects may not represent the full impact. This study aims to estimate potential benefits in life time from adhering to daily ambient PM2.5 concentration standards/guidelines. Methods: This study evaluated the relationship between daily ambient PM2.5 level and YLL using a two-stage approach with generalized additive models and meta-analysis. Potential life expectancy gains were then estimated by presuming that daily PM2.5 levels were in compliance with the Chinese and WHO standards. In addition, the attributable fraction of YLL due to excess PM2.5 exposure was also calculated. Results: During 2013–2016, 459, 468 non-accidental deaths were recorded in the six cities of Pearl River Delta, China. Each 10 μg/m 3 increment in four-day average (lag03 ) level of PM2.5 was related to an increment of 13.31 [95% confidence interval (CI): 5.74, 20.87] years of life lost. Implementation of the WHO guidelines might avoid 180, 980.83 YLLs (95% CI: 78, 116.07, 283, 845.60), which corresponded to 0.39 (95% CI: 0.17, 0.62) years of increased life time per death. Additionally, an estimated 0.15% (95% CI: 0.06%, 0.23%) or 2.04% (95% CI: 0.88%, 3.20%) of YLLs could be attributed to PM2.5 exposures higher than the Chinese or WHO guidelines, respectively. Conclusions: This study suggests that people might live longer by controlling daily PM2.5 concentration and highlights the need to adopt stricter standards in China. Highlights: We estimated the life time gain by attaining daily PM2.5 standards. Life time might increase by 0.39 years for each death by attaining WHO's guideline. Up to 2.04% of YLL could be ascribed to PM2.5 exposure higher than WHO's guideline. More ambitious target for PM2.5 control should be employed to improve public health.